Multiple Spinal Tuberculosis with Severe Kyphosis: A Case Report - Chen, Liyi; Liu, Chong; Ye, Zhen; Liang, Tuo; Huang, Shengsheng; Chen, Jiarui; Chen, Tianyou; Li, Hao; Chen, Wuhua; Sun, Xuhua; Yi, Ming; Jiang, Jie; et al. (Frontiers in Surgery, 2022)
BACKGROUND The purpose of this study was to analyze the clinical efficacy of a patient with multiple tuberculosis of the spine combined with severe kyphosis. CASE SUMMARY A 56-year-old male patient presented with low back pain with numbness and fatigue in both lower extremities for 5 months. Chest and back showed intermittent acid pain. The patient had not a history of constitutional symptoms. Preoperative X-ray and CT examination revealed multiple vertebral segmental bone destruction, multiple abscess calcification, and severe scoliosis. Preoperative MRI examination showed that the tuberculous abscess broke through the spinal canal and compressed the spinal cord and nerve roots. The patient underwent posterior lumbar abscess debridement, expanded decompression of the spinal canal, and nerve lysis in our hospital. The operation time was 70 minutes, and the intraoperative blood loss was 200ml. The postoperative drainage volume was 250ml. The patient was hospitalized for a total of 13 days, and the patient's vital signs were stable before and after surgery. The patient was satisfied with the treatment. CONCLUSION For the patient with multiple spinal tuberculosis complicated with severe kyphosis and multiple calcified abscesses in this study, we considered performing abscess debridement to relieve the symptoms of back pain and achieved good clinical efficacy.